79.4k views
1 vote
Z is the midpoint of YA. If YZ = x + 12, and ZA = 6x - 13, what is YA?

User Ana Borges
by
5.3k points

1 Answer

5 votes

Answer:
YA=7x-1

Explanation:

You know that "Z" is the midpoint of "YA". This means the following:


YZ+ZA=YA

Now, you know that the expression for "YZ" is:


YZ = x + 12

And the given expression for "ZA" is:


ZA = 6x - 13

Knowing these expressions, you can substitute them into
YZ+ZA=YA, as following:


( x + 12)+(6x - 13)=YA

Finally, you must add these expressions in order to get "YA".

Therefore, this is:


x + 12+6x - 13=YA\\\\7x-1=YA\\\\YA=7x-1

User Dajobe
by
4.8k points